Association Between Organizational Capacity and Scope Among Lebanese Nonprofits. Issue 2 (4th March 2019) - AbouAssi, Khaldoun; Makhlouf, Nadeen; Tran, Long
Abstract: Nonprofits' capacity and scope can impact organizational performance, separately and jointly. Yet, the relationship between the two constructs remains unexplored. In this article, we examine the association between organizational capacity and scope. Relying on a dataset of environmental nonprofit organizations in Lebanon, we find that, when examined separately, human resources and external relations capacities are significantly associated with single-domain organizations while strategic planning and financial capacities are significantly associated with multiple-domain organizations. When considered together, however, external relations lose such association. Implications for practice and future research on the effect of organizational scope and capacity on nonprofit performance are discussed.